Risk of Children Born with Autism Spectrum Disorders Reviewed from Prenatal Factors - Rahmahtrisilvia, Rahmahtrisilvia; Rahmah, Inas Zahra; Amani, Risca; Efrina, Elsa; Zulmiyetri, Zulmiyetri; Taufan, Johandri; Kusumastuti, Grahita (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
One of the factors causing a child to be born with Autism Spectrum Disorder (ASD) is prenatal, which is when the child is still in the womb. This study aims to find out what prenatal factors affect children born with ASD. The research method used is quantitative descriptive with a retrospective approach. Data was collected by distributing online questionnaires to 33 respondents. The data were analyzed by univariate. The results showed that 51.5% of the risk of ASD children increased in YPPA when the mother was exposed to cigarette smoke, which was 17 people. Maternal emotional state factors 15.2%, complications during pregnancy 12.1%, drug consumption 21.2%, disease history 9.1%, and nutritional state 15.2%. There are no factors that cause children to be born with ASD from maternal age and gestational age. Exposure to secondhand smoke has a significant impact on the risk of children born with ASD